Implementation Curriculum Merdeka in the Study of English at the Senior High School Informatika Tanah Merah Bangkalan - Riza Aulia Widyaningsih; Ashvia Romadona (PT FORMOSA CENDEKIA GLOBAL, 2023)
The curriculum is a benchmark in the management of education because, without it, the learning process will not be implemented. But the Curriculum that exists in Indonesia is often changed according to the rules of the performance of the Minister of Education, so that the polemics are on the ground both in terms of pupils and teachers in the application of learning processes, as well as the latest curricula is independent curriculums, where the concept of the independent currículum is deep concept in strengthening competence, where pupils are required to deepen interests and talents, so in the face of the revolution 4.0 pupils were required to be able to collaborate both in the terms of Information Technology and English Language that will be continuous related to the 4.0 revolution for that purpose the implementation of the free curricular in the learning of English language can integrate in the era in the Age of the 4.0 Revolution. As far as the method used is qualitative, with the presence of this research, we can know that the application of independent curriculum in learning English at the SMAS School of Informatics of the Red Earth has been well implemented.